The irritable bowel syndrome. - Francis, C. Y. (BMJ Group, 1997)
Irritable bowel syndrome is a common disorder varying in severity from trivial to incapacitating. The pathophysiology and epidemiology are gradually being unravelled and it is now becoming apparent just how poor the quality of life of some of these patients can be. It is no longer acceptable practice to diagnose the condition and discharge the patient on a high fibre diet, particularly as the latter can often make the situation worse. Although hard to treat, worthwhile responses can be achieved by careful targeting of therapy to the many different facets of the disorder.